CULTURAL HERITAGE REPOSITORY - Grebeža, Kristīne; Abuže, Anda; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
The author of the article develops a Heritage object database on the DSpace platform, which would provide an international heritage ontologies, so to the digital media for object metadata and objects, documents, articles, images, and 3d (three Dimensions) storing virtual 3d objects. To create the required metadata module, the authors conducted heritage ontologies standards and 2 Digital museum metadata analysis by comparing the descriptive data. By performing metadata analysis, author have created the descriptive data sets that will be used by the new system. The newly acquired metadata set will be appropriate for both the Catalog of national Museums and the CIDOC standard.